Pola kecenderungan migrasi kaum muda perdesaan dan pengaruhnya terhadap regenerasi petani di Provinsi Jawa Timur: The patterns of migration tendency of rural youth and their impact on farmer regeneration in East Java Province - Yudhistira Saraswati (Analisis Kebijakan Pertanian, 2025)
Migration has led to a decline in young human resources, which can harm the agricultural sector in rural areas. This study aims to analyze migration trends and their influence on farmer regeneration in the place of origin. Respondents were senior high school students from farming families in Ngawi and Pacitan Regencies, East Java Province, who were selected randomly. The study employed a quantitative descriptive and inferential approach, with analysis of the relationships among factors influencing migration decisions conducted using Pearson’s correlation test. The results show that the majority of respondents decided to migrate after graduating from school. The migration tendency pattern was permanent migration. Internal factors, the tradition of migrating, and perceptions related to regional development did not influence the decision. External factors that influenced the decision were perceptions of migration and agriculture. The migration decision led to a low interest among young people in continuing the family farming business or starting an on-farm agricultural enterprise. Perceptions of agriculture were low, as respondents viewed agriculture as underdeveloped, lacking innovation, unprestigious, and unreliable as a primary source of income. As a result, farmer regeneration does not occur, potentially threatening the sustainability of on-farm agricultural businesses. Efforts to shift this perception can be made through outreach or campaigns using relevant approaches, such as producing content on promising agricultural innovation. Stakeholders’ support is necessary to ensure the stability of the farming business and to encourage the private sector to promote a positive image of agriculture, attracting rural youth to work in this sector.